Rates and Risk Factors for Unplanned Emergency Department Utilization and Hospital Readmission Following Bariatric Surgery. Issue 5 (May 2016) - Telem, Dana A.; Yang, Jie; Altieri, Maria; Patterson, Wendy; Peoples, Brittany; Chen, Hao; Talamini, Mark; Pryor, Aurora D.
Abstract : Objective: To identify unplanned emergency resource utilization in the perioperative period following bariatric surgery. Summary of Background Data: Avoidable emergency department (ED) utilization and hospital readmissions pose a significant economic burden to our healthcare system. The extent of this problem is poorly studied in the bariatric literature. Methods: Using New York statewide longitudinal administrative data, 38, 776 patients, who underwent primary bariatric surgery from 2010 to 2013, were analyzed. Multiple logistic regression models analyzed all variables with P < 0.05 on univariate models. Results: The 30-day unplanned ED utilization rate was 11.3% and 30-day hospital readmission rate was 5.3%. ED visits resulted in an inpatient admission 34.9% of the time. In total, 17.5% had 2 or more 30-day unplanned ED presentations. Patients presenting to the ED were more likely to be black, have pulmonary disease, be insured by the Centers for Medicaid and Medicare Services, travel further distances for index procedure, and have a surgical procedure other than gastric banding. In total, 46.7% presented to a nonindex hospital and 32.5% were admitted. Patients presenting to a nonindex hospital were significantly less likely to be admitted than those presenting to an index hospital. Conclusions: Unplanned perioperative healthcare utilization is a significant burden incurred by the bariatric population. A clear opportunity is identified for improvement in healthcare delivery—particularly for high-risk and high-frequency utilizers. Presentation to nonindex hospitals has important implications to the accuracy of current patient safety and quality outcomes measures. System measures designed to capture all unplanned resource utilization, not just those to index hospitals, are crucial for accurate evaluation.